Mural Painting of a Roman Lady from Viminacium: From Roman Matron to the Modern Icon - Jelena Anđelković Grašar; Milica Tapavički-Ilić (EXARC Journal, 2015)
During the late antiquity, fresco decorated tombs had a prominent place in funerary practice. All of the scenes and motifs within tombs are dedicated to the deceased persons and their apotheosis. Usually painted on the western wall of the tomb, these portraits could represent a deceased married couple or sometimes individuals. Examples of deceased married couples, depicted as master and mistress of the tomb, can be seen in the tombs of Beška, Serbia (Đurić 1985a, 5-18; Marijanski-Manojlović 1987, 17-32), Silistra, Bulgaria (Димитров and Чичикова 1986; Danov and Ivanov 1980, 105-121; Atanasov 2007, 447-468), Osenovo, Bulgaria (Pillinger, Popova and Zimmermann 1999, 14), Plovdiv, Bulgaria (Овчаров and Ваклинова 1978, 26-27) and Thessalonica, Greece (Dunbabin 2003, 454).